A Generalized Parameter Tuning Method of Proportional-Resonant Controllers for Dynamic Voltage Restorers - Phuong Vu; Ngoc Dinh; Nam Hoang; Quan Nguyen; Dich Nguyen; Minh Tran (Institute of Advanced Engineering and Science, 2018)
Temporary voltage swells and sags appear with high frequency in electric power systems, and they significantly affect sensitive loads such as industrial manufacturing or communication devices. This paper presents a strategy to design proportional-resonant controllers for three full-bridge voltage-source converters with a common DC-link in dynamic voltage restorer systems. The proposed controllers allow the system to quickly overcome temporary unbalanced voltage sags. Simulation results carried out in MATLAB/Simulink and experimental results implemented in a Typhoon HIL402 device demonstrate the ability of the proposed design method. The results show that the system with the proposed controllers can ride-through single-phase or double-phase voltage sags up to 55% and three-phase voltage sags up to 70% in a duration less than one grid-voltage cycle.